Anthropogenic influence on the changing likelihood of an exceptionally warm summer in Texas, 2011. Issue 7 (3rd April 2015) - Rupp, David E.; Li, Sihan; Massey, Neil; Sparrow, Sarah N.; Mote, Philip W.; Allen, Myles
Abstract The impact of anthropogenic forcing on the probability of high mean summer temperatures being exceeded in Texas in the year 2011 was investigated using an atmospheric circulation model to simulate large ensembles of the world with 2011 level forcing and 5 "counterfactual" worlds under preindustrial forcing. In Texas, drought is a strong control on summer temperature, so an increased frequency in large precipitation deficits and/or soil moisture deficits that may result from anthropogenic forcing could magnify the regional footprint of global warming. However, no simulated increase in the frequency of large precipitation deficits, or of soil moisture deficits, was detected from preindustrial to year 2011 conditions. Despite the lack of enhancement to warming via these potential changes in the hydrological cycle, the likelihood of a given unusually high summer temperature being exceeded was simulated to be about 10 times greater due to anthropogenic emissions.